Whispering gallery modes on optical micro-bottle resonator for humidity sensor application - Johari, Md Ashadi Md; Abdul Khudus, Muhammad Imran Mustafa; Jali, Mohd Hafiz; Al Noman, Abdullah; Harun, Sulaiman Wadi (Elsevier, 2019)
We investigate the use of a class of whispering gallery mode optical resonators, namely, optical microbottle resonators (MBR) as a relative humidity (RH) sensor. The MBR is fabricated via the so-called “soften-and-compress” method to create a bulge (bottle) structure with a bottle diameter D b =190⁡μm, stem diameter of D s =125⁡μm and bottle length of L b =182⁡μm. The MBR is then optically excited by using a 2 μm optical microfiber and was found to have a Q-factor of >10 4 . The MBR was then employed as a humidity sensor with a RH range of between 40%–80% and the performance is compared with a no-MBR microfiber. The MBR RH sensor was found to have a sensitivity 0.0487 dB/%, linearity >90% and P-value >10 5 and is superior to the no-MBR microfiber in all measured parameters. The MBR RH sensor was also found to have good repeatability and stability over a period of 60 s. The wavelength shifted for the MBR is 0.03 nm greater than no-MBR. © 2019 Elsevier GmbH